RESPON PETANI TERHADAP USAHATANI KELOR DI DESA NOELBAKI KECAMATAN KUPANG TENGAH KABUPATEN KUPANG - Vikror Manafe; Marthen Robinson Pellokila; Kudji Herewila (Undana Press, 2023)
The study is purposed to figure out the factory that affecting the response of the farmer to undertake moringa farming, because it is one of farming field that just started to develop and it has economic value. The samples of this study were the farmer in Noelbaki villaege. According to purposive sampling method in oder to perform collecting data was carried out by questionnaires consequently tabulating analyzing with logistic regression model. Further, dependent variable (Y) is marked with number 1 as respons and number 0 as unrespons. The result of this study were showing factory that affecting farmer’s respon towards moringa farming are the Age (X1), the Experiece (X4), the Distance of home to farming location (X6), the Distance of farming location to market(X8).